Geography of transnational knowledge flows from China: Distance, Pipelines and Hierarchy? - Jiaqian Zhang; Yuefang Si; Jianhui Yu (PLoS ONE)
With the rise of China's innovation capacity and position in the global innovation system, an increasing number of scholars are paying attention to the knowledge diffusion from developed economies to China. However, there is less research looking into the destinations of transnational knowledge diffusion from China and their influencing factors from the dynamic perspective. This study uses USPTO data for the period 2003-2022 to illustrate the spatial pattern of Chinese transnational knowledge diffusion and estimates the impact of geographical distance, knowledge pipelines, and hierarchy in the global innovation system. We find that the global innovation system has been comparatively stable, but that China has successfully transitioned from the periphery to being a semi-peripheral and then a core country. The knowledge transfer from China occurred firstly to core and semi-peripheral countries, as the reversed knowledge flow, and then to developing countries along the "Belt and Road" initiative with an increasingly important role in "South-South Cooperation". Regarding its influencing factors, geographical distance is significant across all periods, highlighting that distance remains an indispensable factor in innovation and knowledge flow. Knowledge pipelines and hierarchy in the global innovation system are conditionally influential. Knowledge pipelines were only significantly positive when China was a semi-peripheral country. Compared with the periphery, the knowledge flow from China increasingly tended towards semi-peripheral countries during its catching-up process, but the knowledge could be accepted by the core countries only during the time when China was a semi-peripheral country. Our research unpacks the complexity of pipelines and hierarchy as influencing factors from the dynamic perspective.